2018
DOI: 10.4085/1062-6050-362-16
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Deep Vein Thrombosis in Collegiate Athletes: An Exploration Clinical Case Series

Abstract: Collectively, both cases reinforce the need for the attending clinicians to perform a thorough history and pay attention to subtle clinical findings, regardless of the relatively low risk in college-aged athletes. Although the Wells' CPRs for DVT can be used as a diagnostic guideline in the general population, it might not fully address the risks inherent in a young, otherwise healthy athletic population. We propose a risk-screening tool that is based on and modified from our experiences with these 2 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As this is a fundamental aspect, we have not discussed this in detail in this study. However, platelet behavior may be influenced by general conditions such as physical trauma, strain, or injury, Platelet sensitivity to external stimuli may be higher in pro-athletes than in non-athletes as the former is more prone to develop venous thromboembolism [50,51]. During physical stress the sympathetic nervous system enters a state of dormancy, and circulating platelets are potentially exposed to adrenergic stimuli, leading to aggregation and activation with an increased release of stored growth factors [52][53][54].…”
Section: Growth Factors and Pf4 Storage In Platelet α-Granulesmentioning
confidence: 99%
“…As this is a fundamental aspect, we have not discussed this in detail in this study. However, platelet behavior may be influenced by general conditions such as physical trauma, strain, or injury, Platelet sensitivity to external stimuli may be higher in pro-athletes than in non-athletes as the former is more prone to develop venous thromboembolism [50,51]. During physical stress the sympathetic nervous system enters a state of dormancy, and circulating platelets are potentially exposed to adrenergic stimuli, leading to aggregation and activation with an increased release of stored growth factors [52][53][54].…”
Section: Growth Factors and Pf4 Storage In Platelet α-Granulesmentioning
confidence: 99%
“… 1 Although physical immobility has been described as a risk factor for DVT, some studies have suggested that competitive athletes could also have a high risk of DVT. 14 , 15 , 16 More recent studies have suggested that COVID-19 exposure might play a role in DVT formation in critically ill patients. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The most common among them are dehydration, intense effort and trauma or injury (Fig. 2) [42]. Dehydration occurs during intense physical activity and makes the blood more likely to form clots [43,44,45].…”
Section: Discussionmentioning
confidence: 99%